(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This presentation will determine the segmental phone units –and their frecuencypresent in the glossalic speech of three Spanish speakers. It will also establish that in glossalic speech the hypothesis of the universal and most frecuent syllabic pattern CV can be applied (Obediente, 2007; Burquest, 2009). To accomplish the objectives, we counted the segments and syllabic structures occurring in 57 phonic groups corresponding to 2 minutes and 44 seconds of glossalic speech. In line with the described research design, we have ordered this work as follows: first, we present a frame of reference which fits this presentation; second, the objectives to be achieved; third, the step by step methodology adopted; then, the analysis and results, with comments for each natural class; and finally, as a conclusion, a summary and discussion of the discoveries, and the possible projections of this work.